The potential of astragalus polysaccharide for treating diabetes and its action mechanism - Liu, Shiyu; Wang, Luyao; Zhang, Zehua; Leng, YuLin; Yang, Yan; Fu, Xiaoxu; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2024)
Type 2 diabetes presents a significant global health burden and is frequently linked to serious clinical complications, including diabetic cardiomyopathy, nephropathy, and retinopathy. Astragalus polysaccharide (APS), extracted from Astragalus membranaceus, exhibits various biochemical and physiological effects. In recent years, a growing number of researchers have investigated the role of APS in glucose control and the treatment of diabetes and its complications in various diabetes models, positioning APS as a promising candidate for diabetes therapy. This review surveys the literature on APS from several databases over the past 20 years, detailing its mechanisms of action in preventing and treating diabetes mellitus. The findings indicate that APS can address diabetes by enhancing insulin resistance, modulating the immune system, protecting islet cells, and improving the intestinal microbiota. APS demonstrates positive pharmacological value and clinical potential in managing diabetic complications, including diabetic retinopathy, nephropathy, cardiomyopathy, cognitive dysfunction, wound healing, and more. However, further research is necessary to explore APS's bioavailability, optimal dosage, and additional clinical evidence.